Effect of the TGF-b signaling pathway on spinal cord ependymoma: A study based on bioinformatics analysis and clinical trials - Fan, Yan-dong; Zhu, Man-li; Muertizha, Mamutijiang; Wang, Jia-ming; Luo, Kun (Folia Neuropathologica, 2025)
This study aimed to identify potential therapeutic targets for spinal cord ependymoma (SCE) and key signaling pathways associated with the transforming growth factor b (TGF-b) signaling pathway through bioinformatics analysis, molecular biology validation, and clinical characteristics. Differentially expressed genes (DEGs) in SCE were identified using the limma package in R, and a Venn diagram was created to obtain the intersection of TGF-b signaling pathway-related genes and DEGs. Next, the clusterProfiler package was employed for enrichment analysis of Gene Ontology and Kyoto Encyclopedia of Genes and Genomes. Also, a protein-protein interaction network of DEGs was constructed using the Search Tool for the Retrieval of Interacting Genes/Proteins website, and Cytoscape was used to visualize and screen the top 20 key genes. Additionally, quantitative real-time polymerase chain reaction and western blot were used to validate the mRNA and protein expression levels, respectively, of SMAD4, TGFB1, and TGFB receptor 1 (TGFBR1) in clinical samples. A total of 61 differentially expressed TGF-b signaling pathway-related genes were associated with 1) biological processes, such as the transmembrane receptor protein serine/threonine kinase signaling pathway, TGF-b receptor signaling pathway, and pathway-restricted SMAD protein phosphorylation; 2) cell components, such as the plasma membrane signaling receptor complex and collagen-containing extracellular matrix; and 3) molecular function, such as SMAD binding, growth factor binding, and cytokine binding. The protein-protein interaction network consisted of 57 nodes and 339 edges, and three key genes (SMAD4, TGFB1, and TGFBR1) were screened. The TGF-b and Hippo signaling pathways may have potential roles in SCE progression, and SMAD4, TGFB1, and TGFBR1 are potential key genes.